Perceived sensory dimension for mental health and well-being: A review - Azi Izwani, Nor Hamzah; Lee, Chia Kuang; Zetty Ain, Kamaruzzaman (Springer, 2020)
The World Health Organisation (WHO) stated that by the year 2020 mental health is expected to be the world’s major concern. It is well known that stress may cause mental health problems such as anxiety and depression. Research shows that stress can be reduced by having or experiencing a green environment. This will stimulate the sensory neurons to have a restorative effect. Therefore, any activity related with a green environment will contribute to maximising sensory effects and optimising positive benefits to health. Having an activity in a green environment will contribute to one’s mental health and well-being. For example, by just viewing greeneries which is a sense of sight, it can contribute to a reduction in the stress level. However, it is best to activate other senses as well. This will definitely affect the quality of life. There are eight perceived sensory dimensions as stated in the literature. Thus, this study aims to critically review the Perceived Sensory Dimensions (PSDs) and green environment, particularly with regard to mental health and well-being. This study is vital to explore the understanding and importance of green environments through the perceived sensory dimensions (PSDs) for mental health and well-being. This study will also contribute to the sustainability of mental health and well-being, especially for ASEAN societies.